A critical discourse analysis of stem cell banking brochures in Malaysia / Ungku Khairunnisa Bt Ungku Mohd Nordin - Ungku Mohd Nordin, Ungku Khairunnisa (2014)
This study employs Critical Discourse Analysis to analyse two brochures of two stem cell banking companies in Malaysia. The primary objective of this study is to look at how these companies construct their identities in their respective brochures. It also looks how social relationships between the companies and their potential customers are constructed through their respective brochures. These companies are Cryocord Sdn. Bhd. and Cellsafe International Sdn. Bhd. Fairclough’s (1992) Three Dimensional Model is used in order to explain the relationship between the text (brochures), discursive practices and the social practises surrounding these brochures. In regards of visual texts, Kress and Van Leeuwen’s (2001) Multimodality Framework is also used to help understand the visual texts embedded. Questionnaires were distributed to ten respondents in order to gather insights and opinions on stem cell banking facilities. The analysis revealed that both brochures used many linguistic devices like transitivity, modality, pronouns and adjectives to promote their companies identities. Visual texts were carefully chosen to help create closer social distance between the companies and the readers. The pictures included also reflected that these companies are sensitive towards the needs of their customers. Most respondents were able to relate to these brochures and used them as guidance in choosing which company to subscribe too. This study is significant as it helps the public to be aware of their roles as consumers as well as their functions in shaping the aforementioned companies’ identities.